Who benefits from GRW? Heterogeneous effects of investment subsidies in Saxony Anhalt - Eva Dettmann; Antje Weyh; Mirko Titze (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We estimate causal employment effects of investment subsidies for treated firms as a whole as well as heterogeneous effects depending on firm characteristics and economic environment. We modify the standard matching and difference-in-difference approach by introducing a combined statistical distance function for matching and flexible durations for outcome differences. We find positive effects of the subsidies on the employment development. We also observe considerable effect heterogeneity.
Keywords: Z0; A11; D61; H20; 330